Revisiting Coastal Spatial Permitting Regulations toward Sustainable Coastal Zone Management - Didi Nursidi; Sugianto Sugianto; Nurul Chotidjah; Roqiyul Ma’arif Syam (Contrarius Indonesia, 2026)
Indonesia faces increasingly complex challenges in managing coastal zones because the rapid expansion of marine spatial utilization has not been followed by an integrated, coherent, and consistent permitting governance system. This study analyzes regulatory inconsistencies in coastal spatial permitting, examines foreign regulatory frameworks through comparative assessment, and formulates a more adaptive and integrated model of coastal permitting governance. The research applies a normative legal method through statutory, comparative, and case study approaches. The findings present three major conclusions. First, Indonesia’s coastal spatial permitting regime contains horizontal, vertical, and temporal inconsistencies among overlapping legal norms and institutional arrangements. These conditions fragment governmental authority, create legal uncertainty, weaken coordination between central and regional institutions, delay approvals for Conformity of Marine Spatial Utilization Activities, and trigger recurring conflicts in coastal space utilization. Second, comparative analysis of the United Kingdom and China demonstrates that effective coastal governance requires integrated spatial planning, strong institutional capacity, and coherent regulatory design. These elements clarify authority allocation, improve licensing efficiency, and strengthen environmental protection. Third, reform of the permitting system through the Coastal Waters Spatial Utilization Conformity framework should integrate planning and licensing mechanisms, apply an ecosystem-based approach, strengthen digital and spatial data systems, expand meaningful public participation, and improve interinstitutional coordination. These measures can create a more equitable, transparent, and sustainable model of coastal governance in Indonesia.